Optimizing The Role Of Indonesia's Islamic Financial Industry :Empirical Analysis Of Its Impact on Economic Growth - Febby Rhamadhani, Rika; Fanani, Ahmad (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2023)
Past research on the financial sector, which includes the whole financial services industry and is connected to economic growth, has remained scarce. The three main Islamic financial industry sectors in Indonesia—Islamic Capital Market, Islamic Banking, and Islamic Non-Bank Financial Industry—and their contributions to economic growth between 2014Q1 and 2021Q3 were empirically studied in the current study. The ARDL Bound-test for Cointegration and Error Correction Model was applied to the quarterly data (ECM). Three of the four research variables—sharia stocks, Sukuk, and sharia insurance—were found to have a considerable impact on GDP, whereas Islamic banking had no such impact. Islamic banks in Indonesia must therefore maximize funding for the productive sector. Future policies ought to take into account maximizing the contribution of the Islamic financial sector to economic growth.